Blinking indexes dynamic attending during and after music listening - Schea Fissel Brannick; Arianna N. LaCroix (Scientific Reports)
Abstract Music’s rhythmic and acoustic structure can shape how attention unfolds over time, but little is known about how music listening influences the temporal dynamics of attention. This study examined whether blinking, a linked marker of attention, entrains to acoustic features of music, and whether this entrainment predicts changes in attention post-listening. Fifty-seven middle-aged and older adults listened to either high dynamic (fast, perceptually complex), low dynamic (slow, perceptually stable), or no music for 10 min before and after completing the Attention Network Test (ANT). Blink probabilities were analyzed in relation to perceptual dynamics during music listening (spectral novelty) and at task-relevant timepoints during the ANT. Spectral novelty in the music predicted non-linear fluctuations in blinking, with high dynamic music eliciting early blink–music coupling and low dynamic music producing delayed, later stage entrainment. After listening, alerting effects differed by music condition: low dynamic music was associated with reduced blinking on double cue trials, suggesting greater cue-based attentional readiness, whereas high dynamic listeners showed increased blinking probabilities, possibly reflecting internally guided task preparation. The low dynamic group also showed enhanced executive control, marked by increased and earlier blinking on high-conflict trials, with greater entrainment also predicting earlier blink onsets. These results suggest that music entrainment supports flexible attentional coordination and may enhance attention in aging through distinct cognitive pathways.